2022
DOI: 10.20945/2359-3997000000450
|View full text |Cite
|
Sign up to set email alerts
|

Time to achieve steady state for an accurate assessment of resting energy expenditure in adolescents with healthy weight and obesity: A cross-sectional study

Abstract: Objective: The present study investigated the time needed to achieve a steady state for an accurate assessment of resting energy expenditure (REE) in adolescents with healthy weight and obesity. Materials and methods: Thirty adolescents aged 12-17 years were assigned to a group with healthy weight (GHW; n = 12, body mass index [BMI] 22.5 ± 3.6 kg/m 2 ) and another group with obesity (GO; n = 18, BMI 34.1 ± 5.2 kg/m 2 ). Participants underwent test-retest reliability of REE assessment as follows: a) 24 h of abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…This way, subjects could remain in the same resting facilities and environmental conditions. Momentary EE was assessed after 3 h of fasting as approximation of resting EE (REE) [ 17 ]. Assessment of momentary EE by ventilated hood was identical for P1 and P2 (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This way, subjects could remain in the same resting facilities and environmental conditions. Momentary EE was assessed after 3 h of fasting as approximation of resting EE (REE) [ 17 ]. Assessment of momentary EE by ventilated hood was identical for P1 and P2 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The measurement with ventilated hood lasted 30 min and data were provided every 5 s. Only data of the last 20 min were used to ascertain a balanced recording of gas exchange rates ( O 2 and CO 2 ) as fluctuations are often seen in the beginning of the measurement due to a slow decrease towards a resting level. From sitting or standing to resting in supine position, there is a decrease in EE which typically takes 10 min to achieve a steady state [ 17 , 18 ]. The Weir equation (Weir, 1949) was used to convert O 2 and CO 2 to EE values.…”
Section: Methodsmentioning
confidence: 99%
“…The results indicated that the prevalence of overweight children increased by 103% and indicators of abdominal obesity increased by 153% during the study period. 21 In addition, a study found a prevalence of 13.6% overweight, 5.1% obesity, and 4.0% severe obesity among children in the state of Acre, Brazil. 22 There are several treatments for obesity and overweight, and physical exercise is one of the key approaches.…”
mentioning
confidence: 99%